From Celebration to Consequence: Case Report of Late Onset Ocular Effects of Firework Injuries - Ranabhat, Sudha; Pahadi, Saurya; Byanju, Raghunandan (Journal of Karnali Academy of Health Sciences, 2026)
Firework-related injuries, particularly ocular trauma, pose a significant public health concern during cultural celebrations. We explore the case of a 20-year-old male who sustained firework-induced ocular trauma at the age of seven, subsequently developing traumatic cataract and glaucomatous optic atrophy.The patient presented with decreased vision and pain in the left eye (LE), 13 years post-injury. He underwent cataract surgery nine years after the incident, with subsequent development of glaucomatous optic atrophy. Examination revealed visual acuity impairment, exotropia, and pupil abnormalities in the LE, along with scleral thinning and corneal opacity. Posterior segment evaluation showed optic nerve cupping and hemorrhages. Gonioscopy indicated angle recession and synechiae in the LE. Optical coherence tomography revealed retinal nerve fiber layer defects. Elevated intraocular pressure in the LE was successfully managed with anti-glaucoma medication.Firework-related ocular trauma can lead to long-term complications, including traumatic cataract and glaucomatous optic atrophy. Timely cataract surgery and vigilant follow-up are essential for early detection and management of secondary glaucoma. Regulatory measures to mitigate fireworkrelated injuries are imperative to prevent such incidents and preserve visual health.